DIFFERENCE IN MORTALITY BETWEEN ACUTE STEMI PATIENTS TREATED WITH THROMBOLYSIS AND PRIMARY PCI - Khan, Qurban; Aziz, Sohail; Zahid, Sarfraz Ali; Siddiqa, Aysha; Rehman, Waheed Ur; Ghani, Imran; Naseem, Shaista (Pakistan Armed Forces Medical Journal, 2015)
Objective: To compare the difference in mortality between acute ST elevation myocardial infarction (STEMI) patients treated with thrombolysis and primary percutaneous coronary intervention (PCI) at the Armed Forces Institute of Cardiology, Rawalpindi. Study Design: Descriptive cross sectional study. Place and Duration of Study: This study was conducted at AFIC/NIHD Rawalpindi from 1st July 2014 to Dec 2014. Material and Methods: We retrospectively reviewed data from the Armed Forces Institute of Cardiology Acute Myocardial Infarction registry of 148 consecutive STEMI patients who were thrombolysed (January 1st 2014 until December 31st 2014), and of 1256 consecutive STEMI patients from the Primary PCI registry (17th October until 26th January 2015). Data on demographic and clinical parameters, and mortality was collected and analyzed using IBM SPSS version 21. Results: Comparison of the primary PCI and thrombolysis groups was as follows – mean age: 58.4 years vs 61.0 years, males: 1144 patients (91.1%) vs 126 (85.1%), females: 112 patients (8.9%) vs 22 (14.9%), smokers: 384 patients (30.6%) vs 28 (19.4%), hypertensives: 370 patients (29.5%) vs 43 (29.1%), diabetics: 237 patients (18.9%) vs 30 (20.3%). The mean door-to-balloon time for primary PCI was 52.0 +/- 0.61 minutes and the mean doorto-needle time was 62.4 ± 1.27 minutes. There were 14 peri-procedural deaths in the primary PCI group (periprocedural mortality rate 1.1%). The in-hospital mortality rate was 3.8% in the PPCI group and 18.9% in the thrombolysis group; Conclusion: Primary PCI is a safer and more effective therapy than thrombolysis for the treatment of acute myocardial infarction.